Globalization for Whom? The US and Europe: A Light House Rroject; Challenging the Ethics of Neoliberalism - Tsiourtos, Constandinos (Études helléniques / Hellenic Studies, 2008)
In modern democratic societies, priorities have been altered through the evolution of capital dynamics and under the catalytic impact of capitalism and its latter vicious version - the neoliberalism - to a big part of the world. In particular, the economic has corrupted those foundations, and established its own system of values. Economic relations are now in the centre of attention whilst societal values and safeguarding of fundamental freedoms have become a tool to be used as a pretext, for those powers that violate them the same time they proclaim to protect them. The globalization ‘movement’ was used mainly for the spread of the capital and not democratic values. Alliances such as NATO and the EU-US transatlantic partnership impose their own agenda to the rest of the world and offer their own version of “virtual peace”. The concept of the Left about a world system should be the first step towards purifying globalization than to demonize it. What the Left has to achieve is a new movement of Left internationalism and it should be initiated within the United Nations system.